OPTIMIZATION OF CORROSION-RESISTANT CONCRETE WITH CHEMICAL ADDITIVES - Abobakirova Zebuniso Asrorovna; Umarov Shodiljon Abdugоfurovich; Mirzababaeva Sakhiba Mirzaakbarovna; Mirzayeva is the daughter of Zarnigor Alisher (Journals Park Publishing, 2022)
Currently, due to the rapid development of the construction industry, the demand for concrete and reinforced concrete structures made using portland cement is increasing. In this regard, one of the priority tasks of the building materials production industry is aimed at modernizing production technologies, improving the quality of manufactured products, and increasing their durability, using chemical additives in the production of concrete and reinforced concrete structures, without reducing their strength.
Keywords: concrete, corrosion, moisture, polymer additive, POLY-ANS, mineral substances, superplasticizer.